The effects of emotional dissonance and employee's empowerment on service quality and customer satisfaction perception: customer level analysis - Ab Aziz, Yuhanis (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The performance of customer contact employees is essential in ensuring the success or failure of the service exchange. Employees’ personal conduct and attitude play an important role in affecting customer’s awareness of the quality of service delivered. This study contributes to the current body of work in the service marketing area by investigating four major constructs; Empowerment, Emotional Dissonance, Service quality and Customer satisfaction and their relationships. The sample comprises of hotel customers. The data was collected using a qualitative interview technique. Findings indicate that empowerment has a relationship with emotional dissonance and empowerment may also have significant influence in managing employees’ emotions at a workplace. Results also reveal that there is a positive relationship between empowerment, service quality and customer satisfaction.